Modular Cognitive-Behavioral Therapy for Body Dysmorphic Disorder: A Randomized Controlled Trial - Wilhelm, Sabine (Behav Ther, 2013)
There are few effective treatments for body dysmorphic disorder (BDD) and a pressing need to develop such treatments. We examined the feasibility, acceptability, and efficacy of a manualized modular cognitive-behavioral therapy for BDD (CBT-BDD). CBT-BDD utilizes core elements relevant to all BDD patients (e.g., exposure, response prevention, perceptual retraining) and optional modules to address specific symptoms (e.g., surgery seeking). Thirty-six adults with BDD were randomized to 22 sessions of immediate individual CBT-BDD over 24 weeks (n = 17) or to a 12-week waitlist (n = 19). The Yale-Brown Obsessive-Compulsive Scale Modified for BDD (BDD-YBOCS), Brown Assessment of Beliefs Scale, and Beck Depression Inventory-II were completed pre-treatment, monthly, post-treatment, and at 3- and 6-month follow-up. The Sheehan Disability Scale and Client Satisfaction Inventory (CSI) were also administered. Response to treatment was defined as ≥ 30% reduction in BDD-YBOCS total from baseline. By week 12, 50% of participants receiving immediate CBT-BDD achieved response versus 12% of waitlisted participants (p = 0.026). By post-treatment, 81% of all participants (immediate CBT-BDD plus waitlisted patients subsequently treated with CBT-BDD) met responder criteria. While no significant group differences in BDD symptom reduction emerged by week 12, by post-treatment CBT-BDD resulted in significant decreases in BDD-YBOCS total over time (d = 2.1, p <0.0001), with gains maintained during follow-up. Depression, insight, and disability also significantly improved. Patient satisfaction was high, with a mean CSI score of 87.3% (SD = 12.8%) at post-treatment. CBT-BDD appears to be a feasible, acceptable, and efficacious treatment that warrants more rigorous investigation.